2018
DOI: 10.1093/jat/bky023
|View full text |Cite|
|
Sign up to set email alerts
|

Case Reports of Fatalities Involving Tianeptine in the United States

Abstract: Tianeptine is a tricyclic anti-depressant that is also known to have opioid receptor activity. We present two fatal cases of tianeptine intoxication in Texas in which tianeptine was used recreationally. The first case involved a 28-year-old white male found alone on the floor of his locked residence. He had a history of drug abuse but no other toxicological findings. The second case involved a 30-year-old white male found on the floor of the bathroom in his home. Drug paraphernalia and bags labeled as tianepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…When sold as dietary supplement, its use might even be a blind spot for early warning systems (Evans-Brown and Sedefov 2018;Griffiths, Evans-Brown, and Sedefov 2013). However, as several case reports highlight the danger of the potentially fatal misuse of tianeptine (Bakota et al 2018;Dempsey et al 2017;Proença et al 2007;Rushton et al 2020), increasing awareness is of critical importance.…”
Section: Discussionmentioning
confidence: 99%
“…When sold as dietary supplement, its use might even be a blind spot for early warning systems (Evans-Brown and Sedefov 2018;Griffiths, Evans-Brown, and Sedefov 2013). However, as several case reports highlight the danger of the potentially fatal misuse of tianeptine (Bakota et al 2018;Dempsey et al 2017;Proença et al 2007;Rushton et al 2020), increasing awareness is of critical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Deaths associated with misuse of tianeptine have been reported outside the United States ( 3 , 4 ). Recently, two deaths that were not reported to NPDS during the study period and were attributed to tianeptine toxicity were reported in the United States in persons who purchased the drug online ( 5 ). …”
Section: Discussionmentioning
confidence: 99%
“…Animal and human studies show that tianeptine is an opioid receptor agonist ( 2 ). Several case studies have reported severe adverse effects and even death from recreational abuse of tianeptine ( 3 5 ). To characterize tianeptine exposures in the United States, CDC analyzed all exposure calls related to tianeptine reported by poison control centers to the National Poison Data System (NPDS) † during 2000–2017.…”
mentioning
confidence: 99%
“…In addition, online discussion communities exist that detail doses to achieve euphoria and discuss potential adverse effects and strategies to treat or prevent withdrawal symptoms (Gupta et al, 2017). Fatal overdoses from the purchase and self-administration of powdered tianeptine from online sources have been reported (Bakota et al, 2018). The purchase of tianeptine from online, unregulated sellers greatly increases the risk for the presence of adulterants (Lauhan et al, 2018).…”
Section: Illicit Usementioning
confidence: 99%